2018
DOI: 10.18512/1980-6477/rbms.v17n3p400-407
|View full text |Cite
|
Sign up to set email alerts
|

Períodos De Dessecação Do Capim Ruziziensis E Seus Efeitos No Desenvolvimento E Produtividade Do Milho

Abstract: RESUMO -Considerando que há relatos de possível intoxicação de milho por causa da dessecação de capim braquiária, o objetivo deste estudo foi determinar o melhor período para semear o milho 'Yield Gard DKB 390 YC' após a dessecação da cobertura. O delineamento experimental foi inteiramente casualizado, com quatro repetições.Os tratamentos consistiram em seis períodos de dessecação do capim ruziziensis (25, 20, 15, 10, 05 e 0 dias antes da semeadura do milho) e uma testemunha sem cobertura. As dessecações foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ipyporã. The sowing delay during the crop season can reduce the yield of successor crops such as soybean and maize (Carmo et al, 2018;Silva et al, 2018;Toller et al, 2018;Almeida et al, 2020). This delay submits the plants to unfavorable conditions of growth and development, that is, greater average temperatures and less rainfall (Toller et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ipyporã. The sowing delay during the crop season can reduce the yield of successor crops such as soybean and maize (Carmo et al, 2018;Silva et al, 2018;Toller et al, 2018;Almeida et al, 2020). This delay submits the plants to unfavorable conditions of growth and development, that is, greater average temperatures and less rainfall (Toller et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Using these doses allowed reaching a mortality rate of 100%. Silva et al (2018) reported desiccation over 95% when they applied 1,440 g a.e. ha -1 of glyphosate on swards formed by U. ruziziensis.…”
Section: Resultsmentioning
confidence: 99%